1999
DOI: 10.1017/s0014479799003063
|View full text |Cite
|
Sign up to set email alerts
|

Multistrata Agroforestry with Beans, Bananas and Grevillea robusta in the Highlands of Burundi

Abstract: Some agronomic, economic and ecological aspects of an agroforestry system combining Grevillea robusta trees, bananas (Musa spp.) and beans (Phaseolus vulgaris) were studied in the subhumid highlands of Burundi. Three densities of G. robusta, 208, 313 and 625 trees ha 71 were interplanted in plots of bananas, beans and a banana±bean mixture. When G. robusta was interplanted with bananas, the tree had a positive eect on banana yield with maximum yield occurring at 300 trees ha 71 . In the presence of beans, bana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 2 publications
(2 reference statements)
2
4
0
Order By: Relevance
“…However, Ntamwira et al (2013;2014) found similar (small) effects of pruning on bush and climbing bean yields. A fraction of 0.70 of total PAR transmitted did not affect bean yields in a study by Akyeampong et al (1999), and this fraction is similar to the fraction found in the non-covered measurement positions ( Figure 2). However, at a more severe pruning regime with only four banana leaves remaining, Ntamwira et al (2013) and Ocimati et al (2019) found that banana yields significantly reduced, and in the latter study even pruning up to seven leaves remaining reduced banana yields.…”
Section: Did Pruning Improve Climbing Bean Yields?supporting
confidence: 77%
See 1 more Smart Citation
“…However, Ntamwira et al (2013;2014) found similar (small) effects of pruning on bush and climbing bean yields. A fraction of 0.70 of total PAR transmitted did not affect bean yields in a study by Akyeampong et al (1999), and this fraction is similar to the fraction found in the non-covered measurement positions ( Figure 2). However, at a more severe pruning regime with only four banana leaves remaining, Ntamwira et al (2013) and Ocimati et al (2019) found that banana yields significantly reduced, and in the latter study even pruning up to seven leaves remaining reduced banana yields.…”
Section: Did Pruning Improve Climbing Bean Yields?supporting
confidence: 77%
“…Our findings suggest that pruning may not have been severe enough to enhance climbing bean yields. The fraction of PAR transmitted through the banana canopy on the pruned plots was 0.43, whereas Akyeampong et al (1999) concluded that a similar fraction of 0.42 of PAR transmitted decreased bush bean yields by 27% compared to a non-shaded control. For climbing bean, internal shading of the bean plants could have reduced light availability even more than is expected in bush bean, which could have contributed to a limited effect of pruning on yield.…”
Section: Did Pruning Improve Climbing Bean Yields?mentioning
confidence: 96%
“…These observations suggest that there was complementarity of resource use between A. acuminata and maize at Thika but neutral or competitive interactions were apparent in all other treatments. The enhanced crop growth adjacent to A. acuminata at Thika is analogous to that reported in Uganda [78,79]. Although G. robusta is popular with farmers in semi-arid and sub-humid areas of Kenya, and has been reported to increase crop yield [80], the results from the Thika and Naru Moru sites clearly indicate otherwise, as has been found in other studies [40,81,82].…”
Section: Tree Phenologysupporting
confidence: 77%
“…It is generally agreed that perennial cropping systems are more suitable for maintenance of soil fertility than annual crop system (van Wambeke 1992). For this reason, multi-strata agroforestry with perennial crops is a promising option for long-term land use (Tomich et al 1998;Akyeampong et al 1999), however, these agroforestry systems require proper species selection and adequate management (Schroth et al 2000). The objective of the present study was to analyze the effects of different Ginkgo and crop combinations on soil chemical properties and enzyme activities, and soil fertility quality.…”
Section: Introductionmentioning
confidence: 99%